Health service quality and outpatient hypertension patient satisfaction: A cross-sectional study - Olidya, Desyoma; Ginting, Rapael; Siagian, Masryna; Yulizal, OK; Lumbantobing, Christina JRE.; Edlin, Edlin; Fibrini, Dewi (Buletin Kedokteran & Kesehatan Prima, 2025)
This study aimed to evaluate the impact of healthcare service quality on patient satisfaction among hypertensive outpatients at Muyang Kute Regional General Hospital. Employing a quantitative, cross-sectional design, data were collected from 79 patients using a questionnaire assessing five service quality dimensions (tangibles, reliability, responsiveness, empathy, and assurance) and overall patient satisfaction. Bivariate analysis, utilizing the chi-square test, was conducted to examine relationships between service quality dimensions and patient satisfaction. Results indicated generally positive perceptions of service quality dimensions, with tangibles, reliability, and assurance rated highly. However, empathy and responsiveness showed higher dissatisfaction rates. Notably, only assurance demonstrated a statistically significant association with patient satisfaction (p=0.002), where patients perceiving "Good" assurance were more likely to report satisfaction. Overall patient satisfaction was mixed, with 54.43% reporting satisfaction and 45.57% reporting dissatisfaction. The study highlights the critical role of staff competence and patient confidence (assurance) in driving satisfaction. Recommendations include targeted interventions to improve empathy and responsiveness, continuous monitoring of all service quality dimensions, and further investigation into potential underlying factors affecting overall satisfaction.